Efl Learners' Comprehension Of English Taboo Words In Internet Meme - Masitha, Pujiana, Agus Wijayanto, Ph.D (2016)
This study was descriptive qualitative study concerning with taboo words. The objects of this studywere to identify type of taboo words in internet meme and measure the students' comprehension of taboo words in internet meme.The data for this study is internet meme taken from some internet source, such as twitter, facebook, instagram, pinterest, path, and tumblr, and the EFL learners' respons about taboo words in internet meme.The technique of collecting which used by the researcher is documentary method. Data were analyzed based on Batistella taxonomy. The result of this study showed that all the types of taboo words based on the taxonomy of Batistella were appeared in internet meme, such as profanity, obscenity, vulgarity, and epithet. The most dominant type of taboo words is epithet and least frequent of taboo language is profanity. The second finding of this study was most of EFL learners had almost no experienced in taboo language.